RE-TRAINING IS INEFFECTIVE IN IMPROVING RELIABILITY OF TIBIAL SPINE MEASUREMENTS AND CLASSIFICATION. Issue 4 (28th April 2020) - Ellis, Henry B.; Zynda, Aaron J.; Cruz, Aristides; Sachleben, Brant; Sargent, Catherine; Green, Daniel; Warnick, Drew; Schmale, Gregory; Jagodzinski, Jason; Rhodes, Jason; Mistovich, Justin; Fabricant, Peter D.; et al.
Background: Treatment decisions for patients with tibial spine fractures heavily rely on radiographic measurements. Therefore, it is important to establish reliability of these parameters to assist with standardizing classification and subsequent treatment decisions. Purpose: To improve upon and subsequently validate a proposed measurement system following a live, in-person case review, re-training, and implementation of a new classification of tibial spine fractures. Methods: Following unacceptable classification reliability amongst the tibial spine research interest group when using the original Meyers & McKeever (M&M) classification, a one-hour, live, in-person case review (n=10) of tibial spine fractures with collective agreement on measurements and classification was performed. Based on discussion, a modification of the original M&M classification was developed to specifically define verbiage that lead to unacceptable variance in the original reliability testing. These included a quantitative definition of posterior hinge and the presence of comminution (Figure 1). New reference guidelines were provided to each reviewer demonstrating specific measurements and modified M&M classification prior to subsequent case review along with a new set of randomized, de-identified images. Forty subjects were included, determined as a precedent based on previous reliability studies. Data were analyzed using kappa and ICC for categorical and continuous variables, respectively. Results: Overall, data from 6 surgeon raters were included on a total of 40 cases. Amongst these raters, all variables demonstrated poor interobserver reliability: maximal posterior displacement (ICC=0.23, 95% CI=0.11-0.38), modified M&M classification (Cohen's Kappa=0.25), amount of comminution (Cohen's Kappa=0.27), and recommended treatment (Cohen's Kappa=0.19). Conclusion: Reliability of radiographic measurements and a modified classification for tibial spine fractures remains unacceptable even amongst a group of surgeon experts. A new classification schema may be needed to help reliably guide treatment decisions for patients with tibial spine fractures. : Figure 1.